A feasibility study of rapid nondestructive detection of total volatile basic nitrogen (TVB-N) content in beef based on airflow and laser ranging technique. (November 2018) - Li, Yanlei; Wang, Wenjuan; Long, Yuan; Peng, Yankun; Li, Yongyu; Chao, Kuanglin; Tang, Xiuying
Abstract: To investigate the feasibility of airflow and laser ranging technique for nondestructively determination of TVB-N in beef, a viscoelasticity detection system was employed to collect deformation information of beef samples. Then 12 characteristic parameters were extracted from deformation curves. Multiple linear regression (MLR), principal component regression (PCR) and partial least squares regression (PLSR) were used to establish prediction models for TVB-N. The results showed that the PLSR model using 12 characteristic parameters performed the best with correlation coefficients in calibration and prediction sets (Rc and Rp ) of 0.847 and 0.821, root mean squared errors in the calibration and prediction sets (RMSEC and RMSEP) of 1.750 and 2.560 mg/100 g. This result demonstrated that it was feasible to use airflow and laser ranging technique for rapid and nondestructive detection of beef freshness. This study made possible that the deformation characteristics of livestock and poultry meat could be expressed in a quantitative method. Graphical abstract: Unlabelled Image Highlights: Propose a new technique with airflow and laser ranging for meat freshness detection. A test instrument was independently developed. Extract several characteristic parameters related to deformation characteristics. The prediction models between beef deformation and TVB-N content were established. It made possible that deformation of meat can be expressed in a quantitative method.